Communications and technology for violence prevention workshop summary - Blakeslee, Katherine M.; Patel, Deepali; Simon, Melissa A.; Institute of Medicine (U.S.) Forum on Global Violence Prevention; National Research Council (U.S.); mPrevent Violence: Communications and Technology for Violence Prevention (Workshop) (2011, Washington, D.C.) (Washington, D.C. The National Academies Press, 2012)
In the last 25 years, a major shift has occurred in the field of violence prevention, from the assumption that violence is inevitable to the realization that violence is preventable. As we learn more about what works to reduce violence, the challenge facing those who work in the field is how to use all of this new information to rapidly deploy or enhance new programs. At the same time, new communications technologies and distribution channels have altered traditional means of communications, and have made community-based efforts to prevent violence possible by making information readily available. How can these new technologies be successfully applied to the field of violence prevention? On December 8-9, 2011, the IOM's Forum on Global Violence Prevention held a workshop to explore the intersection of violence prevention and information and communications technology. The workshop - called "mPreventViolence" - provided an opportunity for practitioners to engage in new and innovative thinking concerning these two fields with the goal of bridging gaps in language, processes, and mechanisms. The workshop focused on exploring the potential applications of technology to violence prevention, drawing on experience in development, health, and the social sector as well as from industry and the private sector. Communication and Technology for Violence Prevention: Workshop Summary is the report that fully explains this workshop
Includes bibliographical references
Title from PDF title page
Keywords: Violence / prevention & control; Social Media; Global Health; Evidence-Based Practice; Telecommunications